ESTUFAS, TELADOS E SUBSTRATOS NO CRESCIMENTO DE MUDAS DE AMOR – PERFEITO (Viola tricolor L.) - VIEIRA, Mariane Tavares,; SOUZA, Larissa Gabriela Pereira,; MARQUES, Ana Letícia Ribeiro,; COSTA, Edilson2 (edilson.costa@uems.br);,; DUARTE, Ítala Layane, (ANAIS DO ENIC, 2023)
-